Secondary metabolites and biodiversity of actinomycetes - Manal Selim Mohamed Selim; Sayeda Abdelrazek Abdelhamid; Sahar Saleh Mohamed (Journal of Genetic Engineering and Biotechnology, 2021)
Abstract Background The ability to produce microbial bioactive compounds makes actinobacteria one of the most explored microbes among prokaryotes. The secondary metabolites of actinobacteria are known for their role in various physiological, cellular, and biological processes. Main body Actinomycetes are widely distributed in natural ecosystem habitats such as soil, rhizosphere soil, actinmycorrhizal plants, hypersaline soil, limestone, freshwater, marine, sponges, volcanic cave—hot spot, desert, air, insects gut, earthworm castings, goat feces, and endophytic actinomycetes. The most important features of microbial bioactive compounds are that they have specific microbial producers: their diverse bioactivities and their unique chemical structures. Actinomycetes represent a source of biologically active secondary metabolites like antibiotics, biopesticide agents, plant growth hormones, antitumor compounds, antiviral agents, pharmacological compounds, pigments, enzymes, enzyme inhibitors, anti-inflammatory compounds, single-cell protein feed, and biosurfactant. Short conclusions Further highlight that compounds derived from actinobacteria can be applied in a wide range of industrial applications in biomedicines and the ecological habitat is under-explored and yet to be investigated for unknown, rare actinomycetes diversity.